PENGARUH BAGI HASIL, INFLASI, DAN BI RATE TERHADAP SIMPANAN DANA PIHAK KETIGA PADA BANK UMUM SYARIAH - Ramadhani, Dyana; Abdullah , Mohammad Faisal (Program Studi Ekonomi Pembangunan, 2021)
This study aims to determine the effect of profit sharing, inflation, and bi rate on deposits of third party Islamic banks. The population used in this study is all Islamic banks registered in Bank Indonesia and Otoritas Jasa Keuangan. The sample in this study used the census method as many as 14 Islamic banks. The data analysis used multiple linear analysis method. The results in this study partially the profit sharing variable and the BI Rate have a significant effect on deposits and third parties, the inflation variable has a negative and insignificant effect on deposits of third party funds. Simultaneously the variables for profit sharing, BI Rate, and inflation have a significant effect on third party funds deposits.